Concepts and trends in healthcare information systems - Lazakidou, Athina A.; Koutsouris, Dionysios-Dimitrios (Annals of Information Systems, 2014)
Concepts and Trends in Healthcare Information Systems covers the latest research topics in the field from leading researchers and practitioners. This book offers theory-driven research that explores the role of Information Systems in the delivery of healthcare in its diverse organizational and regulatory settings. In addition to the embedded role of Information Technology (IT) in clinical and diagnostics equipment, Information Systems are uniquely positioned to capture, store, process, and communicate timely information to decision makers for better coordination of healthcare at both the individual and population levels. For example, data mining and decision support capabilities can identify potential adverse events for an individual patient while also contributing to the population's health by providing insights into the causes of disease complications. Information systems have great potential to reduce healthcare costs and improve outcomes. The healthcare delivery systems share similar characteristics with most service and productive organizations, but also exhibit specific characteristics, which are related to the complexity and diversity of healthcare production, including the dissimilar ways healthcare professionals discharge their clinical tasks. New requirements and technological advances occurring in healthcare, information systems, and information technology have influenced the evolving role of healthcare information systems and related technology, and this book will help bring the field up to date. The topics covered include computer based simulation and modeling for healthcare treatment, training, and optimization, role of healthcare information systems in improving care in different national health systems, role of healthcare information systems in fostering improved health and healthier lifestyles, challenges and impact of data standards on healthcare delivery, role of information technology in evidence-based medicine, information systems in personalized medicine, e-health Policy, privacy, security and trust issues with e-health solutions, mobile healthcare initiatives and social media in healthcare.